PENGARUH MOTIVASI KERJA, KOMPENSASI DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PT. INTEGRATED SERVICE SOLUTION (ISS) INDONESIA SURABAYA - Abd. Hakam; Abd Kodir Djaelani; Afi Rahamat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTWriting this paper aims to determine how the influence of work motivation, compensation and promotion on the performance of employees of PT. ISS Indonesia Surabaya. PT. Integrated Service Solution (ISS) Indonesia is a service company that is engaged in the outsourcing system. The population in this study is from data obtained using a questionnaire or questionnaire from employees of PT. ISS Indonesia in Surabaya numbered 102 employees. Sampling in this study using the Slovin formula with simple random sampling technique obtained as many as 51 respondents. Data analysis was performed using multiple linear regression analysis with the help of SPSS for Windows version 20. The type of research used was explanatory research using a quantitative approach. In this study the results obtained indicate that work motivation, compensation and promotion are partially positive and significant effect on the performance of employees of PT. ISS Indonesia Surabaya and work motivation, compensation and promotion simultaneously have a positive and significant effect on the performance of employees of PT. ISS Indonesia Surabaya.Keywords: Work Motivation, Compensation, Position Promotion and Employee Performance.